2018
DOI: 10.1016/j.compstruct.2018.08.046
|View full text |Cite
|
Sign up to set email alerts
|

A strain-based criterion for failure load prediction of steel/CFRP double strap joints

Abstract: One of the most effective approaches to improve the strength of steel structures is using the carbon fiber reinforced polymer (CFRP) as externally-bonded sheets. In this paper, a strain-based failure criterion, namely the critical normal strain (CNS) is employed to predict the failure load of adhesively bonded double strap joints which are made of CFRP and steel plates. According to this approach, the adhesive joint fails when the normal strain along the adhesive mid-line attains a critical value at a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The failure assessment of double strap joints made with steel and CFRP was performed by Majidi et al, 36 and by using a proposed approach (point stress method), the authors were able to predict the failure load under quasistatic conditions, a method found to be in good agreement with experimental tests. More recently, Razavi et al 37 presented a strain-based criterion to predict the failure load of the same type of joints (based on a two-dimensional linear elastic finite element analysis), being able to present a good consistency in its predictions and comparing well with experimental results found in the literature.…”
Section: Introductionmentioning
confidence: 89%
“…The failure assessment of double strap joints made with steel and CFRP was performed by Majidi et al, 36 and by using a proposed approach (point stress method), the authors were able to predict the failure load under quasistatic conditions, a method found to be in good agreement with experimental tests. More recently, Razavi et al 37 presented a strain-based criterion to predict the failure load of the same type of joints (based on a two-dimensional linear elastic finite element analysis), being able to present a good consistency in its predictions and comparing well with experimental results found in the literature.…”
Section: Introductionmentioning
confidence: 89%
“…The optimized adhesive was given the name "PA-30". Dispersion of MWCNTs in DMF was performed using ultrasonic bath [38]…”
Section: Methodsmentioning
confidence: 99%
“…The size of the finite elements assigned for the steel plates was selected based on the results provided by the preliminary analysis, which had shown that no significant effects were produced at this level. A mesh refinement with the level set to 0.1 (0.1 mm maximum length of the mesh elements) was performed for the edges of the bond area since these regions are susceptible to stress concentrations [43,44]. The transition between the meshing areas with different elements and distinct refinement levels has been progressively achieved, with a reduced gradient, through specific zones, also called smooth transition regions.…”
Section: Finite Element Model Descriptionmentioning
confidence: 99%